Sustainable Building Materials: Ferro Cement - Clay Roof Tile - Umar, Kassim, Hj.; Kamarudin, Mohd Nor, Prof. Dato' Dr.; Wan Mohd Sabki, Wan Omar; Nor Ashikin, Ahmad; Mokhzani Khair, Ishak (Malaysian Invention and Design Society (MINDS), 2010)
Umar Hj Kassim and his team won bronze at 21st International Invention, Innovation and Technology Exhibition (ITEX) 2010, 14th - 16th May 2010 di Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.